Voice F0 responses elicited by perturbations in pitch of auditory feedback in individuals that stutter and controls - Bauer, Jay J.; Hubbard Seery, Carol; LaBonte, Rachelle; Ruhnke, Lauren (The Journal of the Acoustical Society of America, 2007)
This study aims to increase our understanding of the underlying mechanisms of vocal control in frequency-altered conditions of auditory feedback for people who do and who do not stutter by assessing the vocal responses to perturbations in pitch of auditory feedback. Past research has shown that the speech of people who stutter improves during frequency-altered feedback, but the mechanisms responsible for this fluency remain unclear. Typically, brief modulations in pitch of voice auditory feedback lead to short-latency corrective voice F0 responses during sustained phonations and inflected speech in nonstuttering individuals. However, data are lacking regarding audio-vocal control mechanisms in individuals that stutter. Brief upward (+) and downward (−) perturbations in pitch (50 or 600 cents in magnitude) lasting 200 ms in duration were introduced intermittently into vocalizing subjects auditory feedback. To date, N=3 moderate to severe developmental stutterers and N=3 age and gender matched control nonstutterers have been tested using the pitch-shift paradigm. Preliminary analyses indicate that compensatory voice F0 responses during sustained vowels are less prevalent, more variable, and slower in latency in individuals that stutter compared to age and gender match controls. However, subject recruitment and analyses related to inflected speech productions are still ongoing.